Ethyl cellulose nanoparticles as a platform to decrease ulcerogenic potential of piroxicam: formulation and in vitro/in vivo evaluation - El-Habashy SE (Dove Medical Press, 2016)
Salma E El-Habashy, Ahmed N Allam, Amal H El-Kamel Department of Pharmaceutics, Faculty of Pharmacy, Alexandria University, Alexandria, Egypt Abstract: Nanoparticles (NPs) have long gained significant interest for their use in various drug formulations in order to increase bioavailability, prolong drug release, and decrease side effects of highly toxic drugs. The objective of this investigation was to evaluate the potential of ethyl cellulose-based NPs (EC-NPs) to modulate the release and reduce ulcerogenicity of piroxicam (PX) after oral administration. PX-loaded EC-NPs were prepared by solvent evaporation technique using different stabilizers at three concentration levels. Morphological examination of selected formulas confirmed the formation of spherical NPs with slightly porous surface. Formulation containing poloxamer-stabilized EC-NPs (P188/0.2), having a particle size of 240.26±29.24 nm, polydispersity index of 0.562±0.030, entrapment efficiency of 85.29%±1.57%, and modulated release of PX (88% after 12 hours), was selected as the optimum formulation. Differential scanning calorimetry demonstrated the presence of PX in an amorphous form in the NPs. Fourier-transform infrared spectroscopy revealed the possible formation of hydrogen bond and the absence of chemical interaction. In vivo study, evaluation of pharmacokinetic parameters, evaluation of gastric irritation potential, and histological examination were conducted after administration of the selected formulation. Time to reach maximum plasma concentration, tmax, of poloxamer-stabilized EC-NPs was significantly higher than that of Feldene® 20 mg capsules (P≤0.001). Encapsulation of the acidic, gastric offender PX into NPs managed to significantly suppress gastric ulceration potential in rats (P≤0.05) as compared to that of PX suspension. A reduction of 66% in mean ulcer index was observed. In conclusion, poloxamer-stabilized EC-NPs (P188/0.2) had a significant potential of offsetting deleterious side effects common in PX use. Keywords: polymeric nanoparticles, poloxamer, NSAIDs, pharmacokinetics, gastric irritation